Biologie et écotoxicologie des véligères de Crassostrea Gigas (Thunberg) dans le bassin d'Arcachon - His, Edouard (Université Bordeaux 1, 1991)
This study analyses the larval recruitment and biology in Crassostrea Gigas, in the Arcachon Bay. Three types of observations were conducted: - a study of the reproduction anomalies in C. gigas between 1976 and 1981. - observations of the particulate nutrition of the veligeres. - ecotoxicologic experiments (organostannic action on oyster reproduction, mostly). The reproduction anomalies in C. gigas could not be attributed to either the genitors' quality or the water quality in the Arcachon Bay, but to a perturbation of the veligeres' trophic regime; the hypothesis of an alteration of the nanoplancton in the Bay, during the summer period, and linked to the action of the organotins is highly considered. The assumption of responsibility of the particulate nutrition by the veligeres in the natural habitat depends essentially on the size of the particles; small size diatoms play an important role in the nutrition of the veligeres in the Arcachon Bay. Larvae show a very specific strategy regarding the reserves accumulated before metamorphosis, and protids are accumulated at the end of the pelagic phase instead of carbohydrates or lipids. C. gigas larvae are very sensitive to aggression factors, and especially to the organostannic action that has a negative impact on their growth, even with concentrations as low as 20 ng.l-1. Nevertheless, the alteregenes' action can be indirect, inhibiting the cell multiplication of the algae used as aquaculture feed and that veligeres feed on. C. gigas larvae can act as a sentinel in the monitoring of coastal ecosystems. (unverified OCR) Cette étude porte sur le recrutement et la biologie des larves de Crassostrea Gigas, dans le Bassin d'Arcachon. Trois types d'observations ont été réalisés : - une étude des anomalies de la reproduction de C. gigas qui se sont manifestées de 1976 à 1981. - des observations sur la nutrition particulaire des véligères. - des expériences d'écotoxicologie (action des organostanniques sur la reproduction des huîtres, en particulier). Les anomalies de la ...